The decline in saving a threat to America's prosperity? - Bosworth, Barry, 1942-; ProQuest (Firm) (Washington, D.C. : Brookings Institution, 2011)
"Examines the decline in saving in the United States over the past quarter-century. Is it a statistical artifact of the official measure of saving? Why don't Americans save? What are the consequences for economic growth, the performance of the aggregate economy, and policy goals?"--Provided by publisher.
Introduction -- Measuring saving -- Why don't americans save? -- Global saving patterns -- Consequences of low saving.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Saving and investment -- United States; United States -- Economic policy; Electronic books